2010
DOI: 10.1007/s10545-010-9073-y
|View full text |Cite
|
Sign up to set email alerts
|

The reality of dietary compliance in the management of phenylketonuria

Abstract: In phenylketonuria (PKU), it is common for blood phenylalanine (Phe) concentrations to be outside optimal target ranges, particularly in teenagers and adults, indicating inadequate compliance. It is well known that significant noncompliance exists, and the situation in PKU would appear no different than other chronic conditions. In PKU, compliance is complex, being subject to diverse definitions, and factors influencing compliance include the nature and nurture of the patient, as well as the inconvenience, cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
147
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 33 publications
1
147
0
2
Order By: Relevance
“…Moreover, the AAM have an unpleasant taste. As a consequence patients often show a low diet adherence, particularly older children and adolescents (Macdonald 2000;Macdonald et al 2010). Especially during adolescence many patients drop out of specialized care (M€ utze et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the AAM have an unpleasant taste. As a consequence patients often show a low diet adherence, particularly older children and adolescents (Macdonald 2000;Macdonald et al 2010). Especially during adolescence many patients drop out of specialized care (M€ utze et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…When examining predictors of the proportion of blood phe concentrations within target range (Table 4), child age was entered first, given previously reported associations with metabolic control (MacDonald et al 2010). Parental age was not selected as a predictor variable given the high correlation with child age (r ¼ 0.73), and perceived support from family was used rather than total social support score given the stronger correlation with percentage of blood phe concentrations in target range.…”
Section: Resultsmentioning
confidence: 99%
“…This correspondence outlined the adverse effects of PKU on the quality of life of patients and their caregivers, especially in childhood when a strict diet is required until the age of 10 years, and in adolescence when the diet compliance proves to be more difficult. In adulthood, self-management of the condition becomes quite challenging and poses great difficulties both psychologically and socially (Feillet et al 2010a;Macdonald et al 2010). The cost, inconvenience, and sometimes difficult access to PKU diet increase the difficulty of adhering to it.…”
Section: Discussionmentioning
confidence: 99%
“…The cost, inconvenience, and sometimes difficult access to PKU diet increase the difficulty of adhering to it. Although there is still debate over whether adult PKU patients need a strict phenylalanine-restricted diet and despite the fact that there are some adults with PKU who do not follow a restricted diet and lead normal lives, many studies have advocated following a restricted diet in adulthood as it has been shown that high phenylalanine levels in adults can have adverse effects on mood, sustained attention, concentration, and cognitive ability (Feillet et al 2010b;Ten Hoedt et al 2011;Macdonald et al 2010;Moyle et al 2007;Simon et al 2008). Restricted diet is also crucial in female adults with PKU planning for a pregnancy, as maternal PKU has been shown to cause fetal abnormalities including microcephaly, congenital heart disease, and mental retardation (Prick et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation